Cardiac repolarization and depolarization in people with Type 1 diabetes with normal ejection fraction and without known heart disease: a case‐control study. Issue 10 (2nd June 2018) - Isaksen, J. L.; Graff, C.; Ellervik, C.; Jensen, J. S.; Rossing, P.; Kanters, J. K.; Jensen, M. T.
Abstract: Aims: To investigate depolarization and repolarization durations in people with Type 1 diabetes, including the relationship to age. Methods: 855 persons with Type 1 diabetes without known heart disease were included and matched with 1710 participants from a general population study. Clinical examinations, questionnaires and biochemistry were assessed. A 10‐second 12‐lead ECG was performed and analysed digitally. Results: QTc was longer in people with Type 1 diabetes compared to controls (414±16 vs. 411±19 ms, P <0.001), and particularly so in young people with Type 1 diabetes. The fully adjusted increase was 13.8 ms (95% confidence interval (CI): 8.6–19.0 ms, P <0.001) at age 20 years and 3.4 ms (CI: 1.5–5.3 ms, P <0.001) at age 40 years. The rate‐corrected QRSc was increased in people with Type 1 diabetes (97±11 vs. 95±11 ms, P <0.001) and was age‐independent ( P =0.5). JTc was increased in the young people with Type 1 diabetes (10.7 ms (CI: 5.4–16.0 ms, P <0.001) at age 20 years), but not in older people with Type 1 diabetes (interaction age‐diabetes, P <0.01). Conclusions: For people with Type 1 diabetes, cardiac depolarization is increased at all ages, whereas repolarization is increased only relatively in young people with Type 1 diabetes. Hence, young people with Type 1 diabetes may be more prone to ventricular arrhythmias. The findings contribute to the understanding of sudden cardiac death in young people with Type 1 diabetes. What's new?: This is the largest matched analysis of electrocardiographic changes in people with Type 1 diabetes without known heart disease and with normal ejection fraction. Depolarization duration is increased in people with Type 1 diabetes; repolarization duration is only increased in young people with Type 1 diabetes. Increased repolarization duration in young people suggests that they may be more prone to ventricular arrhythmias, potentially explaining the dead in bed syndrome and the increased risk of sudden cardiac death. Increased resting heart rate is present in people with Type 1 diabetes even without clinical heart disease.